THE ROLE OF TECHNOLOGY IN IMPLEMENTING KURIKULUM MERDEKA : A REVIEW OF CURRENT PRACTICES - Pretty Elisa Ayu Ningsih; Mike Nurmalia Sari (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The integration of technology into the Kurikulum Merdeka framework offers significant potential for enhancing student engagement and improving learning outcomes. This study explores the impact of various digital tools and resources on the educational experience within Indonesian schools. Through an examination of current practices, challenges, and benefits, the research highlights how Learning Management Systems (LMS), interactive multimedia, and adaptive learning technologies contribute to personalized and engaging learning environments. The findings indicate that technology can effectively support Kurikulum Merdeka's goals of fostering critical thinking, creativity, and student autonomy. However, challenges such as infrastructure disparities, teacher training, and resistance to change need to be addressed to fully realize the benefits of technology integration. This study provides valuable insights into how technology can be leveraged to enhance the implementation of Kurikulum Merdeka and improve educational outcomes.